Effect of different drying techniques on drying kinetics, nutritional components, antioxidant capacity, physical properties and microstructure of edamame. (30th March 2022) - An, Nan-nan; Sun, Wei-hong; Li, Bing-zheng; Wang, Yong; Shang, Nan; Lv, Wei-qiao; Li, Dong; Wang, Li-jun
Graphical abstract: Highlights: The effect of five drying methods on dehydration feature of edamame was studied. Different drying methods had a significant impact on the quality of dried edamame. Page model was the most suitable for describing the drying kinetics of edamame. Pulse-spouted microwave vacuum drying exhibited higher quality attributes. The porous structure improved the rehydration and the texture of the sample. Abstract: The present study aimed to investigate the effect of hot air drying (HD), microwave rolling-bed drying (MRD), hot air microwave rolling-bed drying (HMRD), pulse-spouted microwave vacuum drying (PSMVD) and freeze-drying (FD) on the drying characteristics, quality properties and microstructure of edamame. Six models were fitted the drying curves, and quality attributes were analyzed. Results indicated that Page model was the most suited model for edamame drying. Compared with HD, MRD and HMRD improved the quality of edamame and decreased the drying time by 45.59% and 36.03% respectively. The FD and PSMVD possessed higher rehydration ability, nutrient retention and antioxidant capacity compared with other methods. Moreover, PSMVD products showed a crunchy texture, the less color change and the shortest drying time (70 min). Microscopy images demonstrated a distinct porous structure in PSMVD, which facilitated the moisture transfer. Overall, PSMVD is a promising dehydration method for obtaining high value-added edamame products.